Internal Communication in Work Environment and Job Satisfaction: An Empirical Insight - Majekodunmi, Samuel Ayodele; Olajide-Arise, Temi Omovigho; Bamidele A. Wale-Oshinowo (Universitas Tidar, 2025)
Investigations into the internal communication strategy and job satisfaction among unionized employees have not been extensively conducted in government-owned tertiary institutions in Nigeria. This gap has led to the existence of misguided directives. The study has two main variables, independent (internal communication strategy), and dependent (job satisfaction). The research focused on exploring the internal communication strategy and job satisfaction of the unionized non-teaching workforce (UNW) in selected government-owned institutions in Lagos State. The study population comprised 4,800 UNW from the University of Lagos and Lagos State University. Employing a mixed technique, the study utilized a multi-stage sampling technique, questionnaires (with a sample size of 357 based on Krecjie and Morgan’s Table), SPSS Version 26, and Nvivo 10 for analysis. Results indicated a positive and statistically significant impact of internal communication on the job satisfaction of UNW in the chosen government-owned universities in Lagos State, with a p-value of 0.000. Thematic analysis revealed that managerial internal communication strategy positively influenced the job satisfaction of UNW. The study concludes, managerial internal communication strategy significantly affects the job satisfaction of UNW in specific government-owned universities in Lagos State. It suggests a policy reassessment for university management to facilitate timely, accurate, trusted, transparent, and reliable information flow, fostering workforce satisfaction and promoting a healthy collaborative work environment. Inclusive in the suggestion is careful implementation of reappraised institutional policy, more so, provision of avenue for transparency in official engagement and reportage. In addition, encouragement of mutual interaction along horizontal and vertical structures within the institution.